A Robustness Test of the Berger Complete Model: Evidence from Germany - Sharma, D (2013)
This piece of work aims to test the robustness of the Berger Complete Model; this is because varying methods of calculating the efficiencies may give rise to different hypotheses and therefore policy decisions. The four hypotheses are SCP, RMP, X-EFF and S-EFF. In order to test this; technical and scale efficiencies were calculated using the Error Component (EC) and Technical Efficiency (TE) models, these were then used in the Berger Complete Model. This study found that there was a difference in outcome when using efficiencies from the EC and TE methods of calculation. When using data from the EC and TE models in GLS estimation there was support for the SCP hypothesis. However when using the GMM estimation, the EC data gave the SCP outcome, whereas the TE data gave evidence for RMP.